The Tenure Arrangement Of Primary Constitutional Organ Leaders In Indonesian Constitutional System - Bayu Dwi Anggono (Constitutional Review, 2016)
The tenure arrangement of primary constitutional organ leaders is required as the implementation of power limitation principle and the manifestation of political equality principle as the characteristic of democratic state. The tenure arrangements of primary constitutional organ leaders in Indonesia have four models: tenure arrangement through the 1945 Constitution, tenure arrangement through Law, tenure arrangement which is not regulated by law but regulated  in the constitutional organs’ internal regulation, and tenure arrangement which is not regulated by law as well as internal regulation. The problem in this paper is: First, how is the arrangement of leadership tenure in the  constitutional organs according to the Indonesian legislation system. Second, how to adjust the arrangement of constitutional organ leader in order to provide legal certainty and prevent conflict that can disrupt organs’ performance. The arrangement through the Constitution is the most powerful model in term of legal certainty regarding that the Constitution is in the highest national legal order and materials related to the structure and organization of primary constitutional organs constitute the Constitution’s substance. The model not regulated in law but regulated in internal regulation prone to cause conflict because every member of the constitutional organs which meets the requirements may change the internal regulation at any time. To avoid this conflict, this paper concludes that it requires the change of regulation regulating the tenure of constitutional organ leaders so that it is no longer regulated in the constitutional organs’ internal regulations, but it is set  in the 1945 Constitution or at least in the Law in order to have a better legal certainty.